Prevalence and factors associated with depressive symptoms in Malay women - Omar Din, Meriam; Mohd. Noor, Noraini (Routledge, 2009)
Background: Due to a dearth of research on depressive symptoms in Malaysia, particularly in Malay women, a community study was conducted to examine the prevalence and factors associated with current depressive symptoms in rural and urban Malay women with low socioeconomic status.